2000
DOI: 10.1084/jem.193.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Negative Selection during the Peripheral Immune Response to Antigen

Abstract: Thymic selection depends on positive and negative selective mechanisms based on the avidity of T cell interaction with antigen–major histocompatibility complex complexes. However, peripheral mechanisms for the recruitment and clonal expansion of the responding T cell repertoire remain obscure. Here we provide evidence for an avidity-based model of peripheral T cell clonal expansion in response to antigenic challenge. We have used the encephalitogenic, H-2 Au-restricted, acetylated NH2-terminal nonameric peptid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
140
5
5

Year Published

2002
2002
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 141 publications
(161 citation statements)
references
References 67 publications
11
140
5
5
Order By: Relevance
“…The data are consistent with other reports showing that the inhibition of proliferation resulted from increased cell death (7,(27)(28)(29). As the proliferative inhibition and apoptotic death of 2C cells were driven by high avidity TCR ligation with alloantigens, we speculate this observed inhibition resembles the activation-induced cell death reported by others (6,7,27,28,30). Fas has been implicated in Ag-activated apoptosis of CD4 ϩ cells (4, 27, 31), but it is not required for apoptosis of 2C cells (data not shown).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…The data are consistent with other reports showing that the inhibition of proliferation resulted from increased cell death (7,(27)(28)(29). As the proliferative inhibition and apoptotic death of 2C cells were driven by high avidity TCR ligation with alloantigens, we speculate this observed inhibition resembles the activation-induced cell death reported by others (6,7,27,28,30). Fas has been implicated in Ag-activated apoptosis of CD4 ϩ cells (4, 27, 31), but it is not required for apoptosis of 2C cells (data not shown).…”
Section: Discussionsupporting
confidence: 83%
“…High dose Ag can paradoxically suppress immune responses in adult animals. In vivo administration of high dose or high avidity myelin basic protein can deplete Ag-specific T cells and abrogate the clinical and pathological signs of experimental autoimmune encephalomyelitis in mice (6,7). Therefore, it has been clearly shown that strong TCR engagement can induce T cell apoptosis in both the thymus and the periphery.…”
Section: Cd28 Signal Enhances Apoptosis Of Cd8 T Cells After Strong Tmentioning
confidence: 99%
“…One level of control resides at the initial clonal activation of the TCR itself by MHC͞peptide complexes and, reminiscent of thymic negative selection, involves antigen-induced apoptosis. For example, a series of experiments by Anderton et al (5) demonstrated that immunization of B10PL mice with the encephalitogenic NH 2 -terminalacetylated nanopeptide from mouse myelin basic protein (MBP), 1-9Nac MBP, induces experimental autoimmune encephalomyelitis (EAE) and triggers the proliferation of a heterogeneous population of T cells that express diverse TCRs with varying affinities for this encephalitogenic peptide (5). Interestingly, mutated forms of 1-9Nac MBP, which bind to MBP-reactive T cells with very high affinity, trigger the T cells to undergo apoptosis and these peptides are incapable of inducing EAE.…”
mentioning
confidence: 99%
“…Lastly, it may induce an active exhaustion of the pathogenic repertoire. In favor of the latter explanation, a published report demonstrated negative selection during the peripheral immune response to an APL (14). These results, however, are somewhat controversial.…”
Section: Resultsmentioning
confidence: 69%